Quality model for the management of ICT in the teaching process for Peruvian educ ational institutions at the secondary level - Moreno Saenz, Jenny (2014)
Due to the importance of raising the academic performance of students in the regular basic education at the secondary level, the work presented in this paper is developed in the framework of Quality Systems for the Management of ICT. The model has developed an implementation guide that allows properly follow procedures for diagnosis and improvement activities. It is based on the Model Cycle Demming Continuous Improvement (PDCA) and the Self-Assessment Standard ISO 9004.2009 also comprehensively considers the processes and strategies of teaching in educational institutions and the educational model of the country. The planning and implementation of self-assessment will reveal what level of maturity is the institution with respect to the management of ICT, to finally act through improvement activities seeking to correct nonconformities to reach the level of maturity No. 1 or the next level of maturity.